Pengaruh Model Pembelajaran Kooperatif Tipe Team Assisted Individualization (TAI) Terhadap Kemampuan Komunikasi Matematis Siswa SMP - Silalahi, Nila Mona (Unika Santo Thomas Medan, 2019)
The purpose of this study was to (1) determine the effect of the cooperative learning model type Team Assisted Individualization (TAI) on students' mathematical communication skills; (2) find out whether theÂ mathematical communication skills of students with the cooperative learning model Team Assisted Individualization (TAI) type are higher than the mathematical communication skills of students with conventional learning. This type of research is experimental research using the pretest-posttest control group research design. The study population was all seventh grade students of Pancur Batu 2 Junior High School consisting of eight classes. The research sample was selected using simple random sampling technique, so that class VII3 was obtained as the experimental class and class VII-5 as the control class with each number of students as many as 32 students. The data used in this study are quantitative data. Based on the analysis of research data, the following results were obtained: (1) the results of analysis and regression obtained that the influence of cooperative learning type TAI (Team Assisted Individualization) had a positive effect with a correlation coefficient of 0.741 and a determination coefficient of 54.8%; (2) the results of the t-test analysis with the value of t count = 5.643 and t table = 1.669 which means t count> t table, then the hypothesis Ho is rejected. So that it can be concluded that the mathematical communication skills of students taught by cooperative learning model type TAI (Team Assisted Individualization) are higher than the mathematical communication skills of students who are taught by conventional learning.